1999
DOI: 10.2144/99263cr03
|View full text |Cite
|
Sign up to set email alerts
|

Green Fluorescent Protein-Based System for Analysis of E-Selectin-Mediated Adhesion

Abstract: Numerous cell-based or cell-free systems for study of selectin adhesion use radiolabeled tracers. However, in addition to handling problems associated with the use of radioisotopes, these assays have difficulty relating a number of counts to a number of adherent cells. Here, we describe an assay that uses the natural fluorescence of the green fluorescent protein (GFP) to measure binding of cells to E-selectin. We elaborated an adhesion system composed of a cell monolayer expressing E-selectin ligand to which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It has been reported by Zöllner and Vestweber [38] that transfection of CHO cells with cDNA for FucT‐VII selectively activated the hamster homologue of the E‐selectin ligand‐1 (ESL‐1) in CHO cells. Similarly, we recently showed that FucT‐VII‐transfected CHO cells adhered well to E‐selectin [31]. Therefore, it was not necessary to transfect the ESL‐1 cDNA in our CHO cell lines to measure E‐selectin adhesion after FucT‐VII transfection.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…It has been reported by Zöllner and Vestweber [38] that transfection of CHO cells with cDNA for FucT‐VII selectively activated the hamster homologue of the E‐selectin ligand‐1 (ESL‐1) in CHO cells. Similarly, we recently showed that FucT‐VII‐transfected CHO cells adhered well to E‐selectin [31]. Therefore, it was not necessary to transfect the ESL‐1 cDNA in our CHO cell lines to measure E‐selectin adhesion after FucT‐VII transfection.…”
Section: Resultsmentioning
confidence: 84%
“…In a reciprocal experiment, we investigated the possibility that HT transfection of CHO/FucT‐VII cells could suppress sLe x expression. In a first series of experiments, a CHO/FucT‐VII clone that expressed 100% sLe x [31] was transiently transfected by pcDNA3/HT construct or pcDNA3 vector alone and checked for sLe x expression. We performed a double‐labelling experiment in order to check whether cells which transiently express H epitope still express sLe x structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation